1C.01: SOLUBLE UROKINASE PLASMINOGEN ACTIVATOR RECEPTOR AS A PROGNOSTIC MARKER OF ALL-CAUSE AND CARDIOVASCULAR MORTALITY IN A BLACK POPULATION. (June 2015) - Botha, S.; Fourie, C.M.T.; Schutte, R.; Eugen-Olsen, J.; Pretorius, R.; Schutte, A.E.
Abstract : Objective: Elevated inflammatory markers such as C-reactive protein (CRP) and interleukin-6 (IL-6) are well-known risk factors for cardiovascular mortality. The less familiar marker, soluble urokinase plasminogen activator receptor (suPAR), is known to predict cancer, infections and all-cause mortality. We determined whether suPAR, CRP and IL-6 are predictive of both all-cause and cardiovascular mortality in a black population, highly burdened by cardiovascular disease and HIV infection. Design and method: We included 1 425 black South Africans, of which 208 died within five years after baseline data collection. EDTA plasma biomarker levels were determined, while all-cause and cardiovascular mortality were used as endpoints. Results: At baseline suPAR, CRP and IL-6 were higher in non-survivors than in survivors (P < 0.001). SuPAR (HR 1.27, 95% CI 1.09–1.48), IL-6 (HR 1.49, 95% CI 1.24–1.78) and CRP (HR 1.39, 95% CI 1.17–1.65) predicted all-cause mortality, while only suPAR (HR 1.40, 95% CI 1.04–1.87) and IL-6 (HR 1.61, 95% CI 1.10–2.35) predicted cardiovascular mortality. The prognostic value of suPAR was independent of IL-6 and CRP (P<=0.015). Figure. No caption available. Conclusions: SuPAR predicted both all-cause and cardiovascular mortality, independent of traditional risk factors, HIV and other inflammatory markers, underlining the prognostic value of suPAR in a black population.